FT-IR Spectroscopic Study Of Terra-Cotta Sarcophagi Recently Excavated In Ainos (Enez) Turkey - Kurap, Gülnur; Başaran, Sait; Çakan, Banu; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2010)
In this study, painting materials and body samples of the decorated terra-cotta sarcophagi, and the body samples of six terra-cotta sarcophagi, recently excavated in Ancient Ainos (Enez) Turkey, were investigated, using the FT-IR spectrometry. EDXRF spectrometry was used as a complementary technique. The experimental results allowed us to identify the mineralogical composition of body samples and main pigments of the decorated parts of the terra-cotta sarcophagi. Spectroscopic results revealed that the investigated samples were fired to a temperature less than 750 degrees C. in the oxidising atmosphere. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ancient terra-cotta sarcophagi; Archaeometry; Inorganic pigments; IR spectroscopy; XRF; decorated potteries; firing temperature; ancient-pottery; micro-raman; ceramics; clay; Arkeometri; İnorganik pigmentler; IR spektroskopisi; dekore çanak-çömlek; fırınlama sıcaklığı; Antik-çömlek; Mikro-Raman; seramikler; kil